Epigenetic Silencing of miR-9 Promotes Migration and Invasion by EZH2 in Glioblastoma Cells - Yi-Chung Chien (Cancers, 2020)
Glioblastoma (GBM) is the most common primary brain tumor in adults. Tumor invasion is the major reason for treatment failure and poor prognosis in GBM. Inhibiting migration and invasion has become an important therapeutic strategy for GBM treatment. Enhancer of zeste homolog 2 (EZH2) and C-X-C motif chemokine receptor 4 (CXCR4) have been determined to have important roles in the occurrence and development of tumors, but the specific relationship between EZH2 and CXCR4 expression in GBM is less well characterized. In this study, we report that EZH2 and CXCR4 were overexpressed in glioma patients. Furthermore, elevated EZH2 and CXCR4 were correlated with shorter disease-free survival. In three human GBM cell lines, EZH2 modulated the expression of miR-9, which directly targeted the oncogenic signaling of CXCR4 in GBM. The ectopic expression of miR-9 dramatically inhibited the migratory capacity of GBM cells in vitro. Taken together, our results indicate that miR-9, functioning as a tumor-suppressive miRNA in GBM, is suppressed through epigenetic silencing by EZH2. Thus, miR-9 may be an attractive target for therapeutic intervention in GBM.